2019
DOI: 10.1182/blood.2019000889
|View full text |Cite
|
Sign up to set email alerts
|

EBV microRNA-BHRF1-2-5p targets the 3′UTR of immune checkpoint ligands PD-L1 and PD-L2

Abstract: This article reports a novel mechanism by which Epstein-Barr virus (EBV) microRNA (miRNA) plays a role to fine-tune the expression of LMP1-driven amplification of inhibitory checkpoint programmed death ligand 1 (PD-L1) and PD-L2 in EBV+ diffuse large B-cell lymphoma. Identification and understanding of the immune checkpoint regulation via miRNA may enable potential novel RNA-based therapies to emerge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 69 publications
2
41
0
Order By: Relevance
“…This indicates that regulation of PD-L1 by miRNAs is very strong, and cells that acquire resistance to these miRNAs could evade host immunity by increasing PD-L1 expression and proliferate as cancers. Interestingly, EBV also encodes an miRNA (miR-BHRF1-2-5p) that negatively regulates PD-L1 expression through binding to the 3 -UTR of PD-L1 mRNA [53]. On the other hand, another study demonstrated that EBV miR-BART-5-5p downregulated PIAS3, a negative regulator of STAT, and thereby upregulated PD-L1 expression in GC [54].…”
Section: Ebvmentioning
confidence: 99%
“…This indicates that regulation of PD-L1 by miRNAs is very strong, and cells that acquire resistance to these miRNAs could evade host immunity by increasing PD-L1 expression and proliferate as cancers. Interestingly, EBV also encodes an miRNA (miR-BHRF1-2-5p) that negatively regulates PD-L1 expression through binding to the 3 -UTR of PD-L1 mRNA [53]. On the other hand, another study demonstrated that EBV miR-BART-5-5p downregulated PIAS3, a negative regulator of STAT, and thereby upregulated PD-L1 expression in GC [54].…”
Section: Ebvmentioning
confidence: 99%
“…Cristino et al reported that when LMP1 was activated, PD-L1 and PD-L2 expression was significantly increased during the transformation of B cells from the late germinal center to early and late activated B cells. Moreover, microRNA-BHRF1-2-5p plays a regulatory role in LMP1 driven PD-L1 and PD-L2 amplification (39). So further identification of microRNAs that target immune checkpoints allow RNA-based therapy.…”
Section: Pd-l2mentioning
confidence: 99%
“…The most frequent inhibitory signal found in EBV-positive gastric cancer is high PD-L1 expression resulting from 9p24.1 amplification (about 11% of cases) [ 134 ], which leads to immune resistance and reduced survival of patients [ 135 ]. EBV gene expression may directly regulate PD-L1 and PD-L2 gene expression [ 136 , 137 ]. The mechanisms by which EBV reduces PD-L1 expression remain to be elucidated in EBVaGC, since EBV LMP-1 and EBNA-2 genes, which can increase PD-L1 expression, are not expressed in EBVaGC.…”
Section: Targeted Therapies For Ebv + Gcmentioning
confidence: 99%